Leadership of Headmaster in Giving Educational Management in High School Nahdlatul Ulama (Smknu) Tulungagung - Soim, Soim (Faculty of Education Universitas Negeri Malang, 2018)
Empowerment activities are considered the most appropriate choice to prepare the educational personnel in an effort to answer the challenges of the times. This research used qualitative research. Data collection used participant observation, in-depth interviews, and documentation. Data analysis starts from reduction, presentation, and conclusion. Data validity is done by the extension of attendance, triangulation, peer discussion and clarification with the informant. The results of research, 1) leadership of the principal in the empowerment of educational personnel using situational approach, this is evidenced by the principal always guiding, fostering, and assist his subordinates in the development of himself; 2) The headmaster in motivating the empowerment of his/her education personnel has the right trick to give motivation to the education personnel in performing various duties and functions. 3) Principal Strategy as an effort of empowerment of education personnel, principals provide opportunities for education personnel to improve their profession through upgrading, training, seminars and workshops, continue the study, requirement plan of education personnel, provide motivation of educational staff, pay attention to the welfare of educational staff, implement cooperation with educational staff and companies or other institutions in the implementation of school programs, fostering discipline of educational personnel.Keywords: principal leadership, empowering educational staff